Intercomparison of in situ CRDS and CEAS for measurements of atmospheric N2O5 in Beijing, China - Li, Z. Y.; Zhu, R.; Xie, P. H.; Wang, H. C.; Lu, K. D.; Wang, D. (Science of the Total Environment, 2018)
Dinitrogen pentoxide (N2O5) is one of the basic trace gases which plays a key role in nighttime atmosphere. An intercomparison and validation of different N2O5 measurement methods is important for determining the true accuracy of these methods. Cavity ring down spectroscopy (CRDS) and cavity enhanced absorption spectrometer (CEAS) were used to measure N2O5 at the campus of the University of Chinese Academy of Sciences (UCAS) from February 21, 2016 to March 4, 2016. The detection limits were 1.6 ppt (1 sigma) at 30 s intervals for the CEAS instrument and 3.9 ppt (1 sigma) at 10 s time resolution for the CRDS instrument respectively. In this study, a comparison of the 1 min observations from the two instruments was presented. The two data sets showed a good agreement within their uncertainties, with an absolute shift of 15.6 ppt, slope of 0.94 and a correlation coefficient R-2 = 0.97. In general, the difference between the CRDS and CEAS instruments for N2O5 measurement can be explained by their combined measurement uncertainties. However, high relative humidity (> 60%) and high PM2.5 concentration (> 200 mu g/m(3)) may contribute to the discrepancies. The excellent agreement between the measurement by the CRDS and CEAS instruments demonstrates the capability of the two instruments for accurately measuring N2O5 with high sensitivity. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: aerosol; air-quality; ambient no3; boundary-layer; cavity; ceas; crds; enhanced absorption spectrometer; induced fluorescence; ionization mass-spectrometry; n2o5; pm2.5; rh; ring-down spectroscopy; temperature-dependence